Optical Coherence Tomography Imaging of Normal, Chronologically Aged, Photoaged and Photodamaged Skin: A Systematic Review - Mamalis, Andrew (Dermatol Surg, 2015)
BACKGROUND: Optical coherence tomography (OCT) is capable of providing a non-invasive real-time cross-sectional image of the skin through the use of light-based interferometry– a method sometimes described as a “light-based ultrasound.” One key application of OCT in dermatology is the visualization of dermal collagen during processes such as chronological aging, photoaging, or photodamage. These skin conditions are typically managed by the practitioner’s subjective assessment of severity and response to therapy. METHODS & MATERIALS: We searched Medline, PubMed, EMBASE, Web of Science, Google Scholar, and Cochrane databases for published literature on the imaging of skin collagen by OCT using the following search terms: “optical coherence tomography,” “OCT,” “skin,” “collagen,” “photoaging,” “wrinkles,” and “photodamage.” RESULTS: Our search resulted in 23 articles investigating OCT skin collagen imaging meeting our search criteria. CONCLUSION: We anticipate tremendous growth in the field of OCT skin imaging that will parallel the development ultrasound technology has experienced over the past 30 years. We foresee that OCT imaging to evaluate skin aging will not only help identify pathological changes earlier, but will also assist evaluation of response-to-therapy longitudinally without biopsy.